HARMONI SOSIAL: Interaksi Sosial Natural-Asimilatif antara Etnis Muslim Cina dan Melayu-Bangka - Abdullah Idi (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
The Reformation era has influenced at least two effects for Indonesiaas a state nation. First, reformation motivated the willingness ofdemocratization as the foundation of legitimacy for the Indonesian existence inthe future. Second, there is a greatest intention from this nation to create a goodgovernance, transparency and accountability for public. Unfortunately, thispolicy has made disharmony and social conflict such as ethnic, religion, evenculture group. At this point, the discussion of local wisdom is appropriate tosupport the unity of Indonesia as the nation. This paper tries to discuss one ofthe practical experiences for interethnic and religion that is Bangka-Malay-Islam for Chinese ethnic. The results of this research show that the harmonyrelationship happened for long time ago in nature without any manipulationson it. This fact supported the unity of Indonesia in the form of unity indiversity.